Promoting positive physical activity behaviors for children and adolescents undergoing acute cancer treatment: Development of the CanMOVE intervention using the Behavior Change Wheel - Grimshaw, Sarah L.; Taylor, Nicholas F.; Conyers, Rachel; Shields, Nora (Frontiers in Pediatrics, 2022)
Background Increasing participation in physical activity has the potential to improve outcomes for children and adolescents with cancer during treatment and into survivorship. The aim of this study is to outline the theoretical process behind development of CanMOVE, a behavior change intervention designed to increase physical activity for children and adolescents with cancer. Study design This study followed a theoretical design process consistent with the Behavior Change Wheel to inform the design of a complex intervention. Materials and methods The three stages of the Behavior Change Wheel intervention design process include: (1) understanding physical activity behavior within the pediatric cancer setting, (2) identifying potential intervention functions, and (3) identifying appropriate behavior change and implementation strategies. Qualitative and behavior change literature relevant to the pediatric cancer treatment setting were used to inform each stage. Results An individualized and flexible approach to physical activity promotion that considers intrinsic factors specific to the child/adolescent and their environment is required. Fifteen behavioral change strategies were identified to form the intervention components of CanMOVE. Implementation strategies were identified to build motivation, opportunity and capacity toward increasing physical activity behaviors. Key intervention components of CanMOVE include standardized assessment and monitoring (physical activity, physical function, and health-related quality of life), provision of an activity monitor to both child/adolescent and parent, and one-on-one capacity building sessions with a healthcare professional. Capacity building sessions include education, goal setting, an active supervised physical activity session, barrier identification and problem solving, and action planning. Conclusion CanMOVE is a novel approach to physical activity promotion in the pediatric cancer treatment setting. The use of a theoretical intervention design process will aid evaluation and replication of CanMOVE when it is assessed for feasibility in a clinical setting. The design process utilized here can be used as a guide for future intervention development.